Synthesis and Properties of Fluoropyrroles and Their Analogues - Serdyuk, Olga V.; Muzalevskiy, Vasiliy M.; Nenajdenko, Valentine G. (Synthesis, 2012)
Pyrroles and indoles are important subunits of many natural products and pharmacologically active compounds. Fluorinated compounds possess a unique complex of physical, chemical, and biological properties that results in their wide application as construction materials, liquid crystalline materials, agrochemicals, and drugs. The review covers the synthesis and properties of fluoropyrroles and their benzo analogues. The literature up to 2011 is highlighted.1 Introduction2 Synthesis of Fluoropyrroles2.1 Functionalization of the Pyrrole Ring2.2 Cycloaddition and Heterocyclization2.3 Other Methods3 Synthesis of Indoles, Indolizines and Deazopurines with Fluorinated Pyrrole Rings3.1 Functionalization of the Pyrrole Ring3.2 Heterocyclizations4 Synthesis of Indoles with Fluorine Atoms on the Carbocycle5 Properties of Fluorinated Pyrroles and Indoles6 Conclusions
Keywords: fluorine; heterocycles; pyrroles; indoles